Penggunaan Bukti Tidak Langsung Dan Penerapan Leniency Program Di Kasus Kartel Indonesia - Winata, Nicky; Tan, Winsherly (JUSTISI, 2022)
Cartels as a Form of Unfair Business Competition KPPU often has difficulty proving it through direct evidence in accordance with Law No. 5/1999, so the alternative used by KPPU to obtain evidence is indirect evidence, and in practice this indirect evidence It is also not easy because it has not been regulated in Law No. 5/1999 so that the Supreme Court has not given any information regarding indirect evidence. The research method used by the author is normative research using library research to obtain data, and there is a need for clarity regarding procedural law from the KPPU. And the Authority of the KPPU in order to facilitate the handling of the KPPU on the Cartel Problem in Indonesia and amid the uncertainty of indirect evidence, the leniency of the program can also be used as an alternative in proving the occurrence of cartel actions carried out by business actors, and the application of evidence is not This directly was also adopted by other countries as well as the leniency program, and Indonesia also needs to follow this step to reduce cartels in Indonesia.